Structural considerations of vitamin D signaling - Molnár, Ferdinand (Frontiers in Physiology, 2014)
Crystal structures represent the static picture in the life of a molecule giving a sneak preview what it might be in reality. Hence, it is very hard to extrapolate from these photos towards dynamic processes such as transcriptional regulation. Mechanistically VDR may be considered as molecular machine able to perform ligand-, DNA- and protein recognition, and interaction in a multi-task manner. Taking this into account the functional net effect will be the combination of all these processes. The long awaited answer to explain the differences in physiological effects for various ligands was one of the biggest disappointment that crystal structures provided since no substantial distinction could be made for the conformation of the active VDR-ligand complexes. This may have come from the limitation on the complexity of the available ligand-VDR structures. The recent studies with full length VDR-RXRα showed somewhat more comprehensive perspective for the 3D organization and possible function of the VDR-RXRα-cofactor complex. In addition to in vitro approaches, also computational tools had been introduced with the aim to get understanding on the mechanic and dynamic properties of the VDR complexes with some success. Using these methods and based on measurable descriptors such as pocket size and positions of side chains it is possible to note subtle differences between the structures. The meaning of these differences has not been fully understood yet but the possibility of a ‘butterfly effect’ may have more extreme consequences in terms of VDR signaling. In this review, the three functional aspects (ligand-, DNA- and protein recognition, and binding) will be discussed with respect to available data as well as possible implication and questions that may be important to address in the future.